A relação esponsal entre Cristo e sua Igreja: a esposa de Cristo na constituição sobre a Igreja do Concílio Vaticano II - Morbiolo, Rodolfo Gasparini (2011)
This bibliography research examined the extent and limits of nuptial Church in the Constitution on the Church of Vatican II. This procedure is justified because of the importance of the issue to the theology of the Catholic Church, once deeply rooted in Scripture and Tradition and its Magisterium, as well as the need to approach the theme of conjugal love in the world today as an instrument of evangelization. Hypothesized that the Vatican did not give importance to the issue as a hermeneutical principle. Having established the veracity of the hypothesis, proposed the re-issue of spousal love their ecclesial communion interface such as communication path of Catholic theology to the scientific world and society today